Integrity of Canine Bone Marow Cells after Cryoprotectant Exposure and Freezing in Liquid Nitrogen - Vodopyanova, L. A.; Zhegunov, G. F. (Problems of Cryobiology and Cryomedicine, 2006)
Canine bone marrow integrity was studied after exposure with cryoprotectants (dimethylsulfoxide, polyethylene oxide with molecular mass of 400, glycerol) and cryopreservation in liquid nitrogen. The integrity of canine bone marrow cells after freezing in liquid nitrogen with no cryoprotectant has been revealed as 6%. During cryopreservation the most effective was found 7% dimethylsulfoxide, preserving more than 80% of cells.